Citizens as Drivers of Change : How Citizens Practice Human Rights to Engage with the State and Promote Transparency and Accountability - World Bank Group (Washington, DC: World Bank, 2017)
Since 2014, the World Bank Group (WBG) has formally mainstreamed citizen engagement in its strategy to end extreme poverty and share prosperity, building on 25 years of emerging practice and research. In the early 2000s, the WBG issued guidance on multi stakeholder engagement to strengthen accountability relationships through citizen participation and ensure that the benefits of development projects reached the poor. Most recently, the development community has acknowledged that development outcomes improve when citizens participate in development, leading to the WBG mandate to mainstream citizen engagement across sectors and countries. The research described in this report, made possible through the Nordic trust fund (NTF), a multi donor knowledge and learning program on human rights for WB staff, aims to deepen understanding of citizen engagement in the development arena through in-depth study of three grassroots initiatives in which empowered citizens played a central role. The research complements existing approaches by explicitly adopting a human rights perspective as well as focusing on organic citizen-led initiatives rather than WBG- or client-initiated projects. In analyzing these cases, this report applies the framework of the World Development Report 2017 (WDR 2017): governance and the law to understand how citizens effectively disrupted the persistent power asymmetries that undermined development outcomes. This report analyzes citizen engagement to reduce corruption in service delivery in three diverse settings: in Afghanistan, improving education outcomes through community-based monitoring of schools; in Paraguay, monitoring sovereign wealth fund resources allocated to education to improve the infrastructure of marginalized schools; and in Serbia, promoting transparency and the integrity of physicians to reduce corruption in the health sector.